2021
DOI: 10.7759/cureus.15618
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of the Mediterranean Diet in the Management of Non-Alcoholic Fatty Liver Disease: A Systematic Review

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the accumulation of intrahepatic fat occurring in the absence of alcohol abuse. The fatty changes in the liver are often the beginning of sequelae of complications, potentially causing steatohepatitis, liver cirrhosis, and hepatocellular carcinoma. The Mediterranean diet is not only a way of eating but is considered a lifestyle and primarily consists of a plant-based diet, with olive oil as the primary lipid. In this study, we reviewed the effectiveness of the Medit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This diet is known as a high-fat diet, with a fat intake of up to 45% of total daily calories[ 35 ]. The basic source of dietary fat in this diet is olive oil[ 33 , 36 ], where oleic acid, a monounsaturated fatty acid (MUFA), is a major component[ 37 ]. The MD is also characterized by high amounts of PUFAs.…”
Section: Associations Between Dietary Patterns and Risk Of Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…This diet is known as a high-fat diet, with a fat intake of up to 45% of total daily calories[ 35 ]. The basic source of dietary fat in this diet is olive oil[ 33 , 36 ], where oleic acid, a monounsaturated fatty acid (MUFA), is a major component[ 37 ]. The MD is also characterized by high amounts of PUFAs.…”
Section: Associations Between Dietary Patterns and Risk Of Nafldmentioning
confidence: 99%
“…It has been proven that MUFA may prevent the development of NAFLD by improving blood lipid concentrations, lowering body fat contents and decreasing postprandial adiponectin expression[ 50 ]. MUFAs (oleic acid) from olive oil have numerous beneficial effects on NAFLD, including decreased oxidized low-density lipoprotein, low-density lipoprotein cholesterol (LDL-C) and TG concentration, without the concomitant decrease in high-density lipoprotein cholesterol (HDL-C)[ 51 ], as well as lowering blood pressure and improving insulin sensitivity[ 37 ]. Additional effects of the MD relate to its polyphenol content.…”
Section: Associations Between Dietary Patterns and Risk Of Nafldmentioning
confidence: 99%
“…The evidence recently provided on the role of MedDiet in the control of nonalcoholic fatty liver disease (NAFLD) is particularly interesting since this metabolic disturbance leads to alterations in lipid metabolism and an increase in CV risk. The meta-analysis conducted by Kawaguchi et al [10 ▪▪ ] reported an improvement in hepatic steatosis and insulin resistance in patients with NAFLD with MedDiet consistent with another systematic review which showed that MedDiet has promising effects in NAFLD through antioxidant and anti-inflammatory effects [11 ▪▪ ]. All these effects support the positive impact of MedDiet on reducing CVD morbidity and mortality [12 ▪▪ ].…”
Section: Mediterranean Dietmentioning
confidence: 66%
“…The effects of bariatric surgery can be mimicked by the very low-calorie diet (VLCD) as shown by the DIRECT trial [94]. Adapting to a Mediterranean diet is a viable option to prevent and treat NAFLD [95]. GLP-1 receptor agonists such as liraglutide [96] and semaglutide [97] can produce up to 10%-15% weight loss and are increasingly used to manage NAFLD [98].…”
Section: Reversal By Weight Lossmentioning
confidence: 99%